Filariasis: diagnosis, treatment and prevention - Palumbo, E. (Acta Biomedica Atenei Parmensis, 2009)
Lymphatic filariasis caused by the mosquitoborne, lymphatic-dwelling nematodes Wuchereria bancrofti and Brigia malayi is still a common tropical parasitic disease and 120 million people are affected in the world, of which two-third in Asia. W. bancrofti is responsible for 90% of this disease, while B. malayi for the remaining 10%. Next to psychiatric illness, this is the leading cause for permanent and long-term disability. Some recent studies have evidenced new aspects in the diagnosis, management and in planning effective strategies for its global prevention. The aim of this up to date is to evidence clinical, diagnostic and therapeutic aspects of this very important infection.